DRAGON FRUIT JUICE ADDITION IN PALM OIL-PUMPKIN EMULSION: PANELIST ACCEPTANCE AND ANTIOXIDANT CAPACITY - Anton Rahmadi; Isak Budi Setionugroho; Yuliani Yuliani; Miftakhur Rohmah (Jurnal Teknologi dan Industri Pangan, 2017)
Addition of dragon juice to emulsion products formulated from olein fraction of red palm oil and pumpkin juice was conducted as an effort to improve the taste thus it can be accepted by consumers. This study aims to (1) observe the acceptance of 60 panelists aged 17-21 years on the parameters of taste, aroma, mouthfeel, color, flavor and aroma of each contributing components of dragon fruit, palm oil, and raspberry flavor with the addition of dragon fruit juice at level 0 (control), 25, 50, and 75% (v/v), and (2) observe the changes in chemical components i.e. vitamin C and total titrable acids, total carotenoid by spectrophotometry, and antioxidant activity by 2,2-diphenyl-1-picrylhdrazyl (DPPH) reduction method. The best formula was the one containing 75% (v/v) of red dragon juice in fresh condition with vitamin C content of 19.32±0.62 mg/100 mL, antioxidant activity of 354.25±0.77 ppm, hedonic color, taste, and viscosity between favorable and very favorable. After 2 weeks of storage at room temperature (28±2ºC), the vitamin C, total carotene, and antioxidant activity of the mixture decreased by 29.72, 15.44, and 46.59%, res-pectively.